EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: TINJAUAN RANAH KOGNITIF, AFEKTIF DAN PSIKOMOTORIK DI SMA MTA SURAKARTA - Nadiyah, Nur Rifqah; Ummu Azka Amalia; Nurul Latifatul Inayati (CV. ADIBA AISHA AMIRA, 2024)
Evaluation in the cognitive, affective and psychomotor domains can provide a comprehensive view of student learning outcomes. This research will focus on evaluating PAI learning at SMA MTA (Majelis Tafsir Al-Qur'an) Surakarta in terms of assessments in these three domains. This research is qualitative in nature with interview and documentation methods as data collection techniques. The source of interview data was PAI teachers and documentation was taken from documents in the form of student report cards and teacher daily journals. The research results show that the evaluation of PAI learning at SMA MTA Surakarta in the cognitive domain is carried out in the form of tests, namely in the form of formative and summative tests. Formative tests are carried out by each PAI teacher in class. Meanwhile, the summative test is carried out by implementing PTS and PAS. The form of the PTS and PAS test is to use an objective test in the form of multiple choices. And in the affective domain, evaluation is carried out by observing or observing students' daily attitudes, which are recorded on an observation sheet in the form of a teacher's journal. Meanwhile, evaluation in the psychomotor domain is carried out by creating works or products in the form of mind mapping.